Craniofacial biology and craniofacial surgery - Sarnat, Bernard G. (Bernard George), 1912-2011 (World Scientific, 2010)
This book is unique. It deals primarily with and brings together a wide-ranging group of essays spanning more than half a century's worth of research done by Bernard G Sarnat. Much of this historical review remains significant and germane today. Some material antedates the emergence of the specialties of craniofacial biology, craniofacial surgery, and bone biology, while many of the reports preceded the period of molecular biology. This book thus represents a fundamental pioneering contribution to a representative portion of the specialties. Building on past data reported by Sarnat, James P Br.